The Tau Mutation of Casein Kinase 1ϵ Sets the Period of the Mammalian Pacemaker via Regulation of Period1 or Period2 Clock Proteins - Maywood, E.S. (SAGE Publications, 2014)
The suprachiasmatic nucleus (SCN) of the hypothalamus is the principal circadian pacemaker in mammals, coordinating daily metabolic and physiological rhythms with the cycle of sleep and wakefulness. SCN neurons define circadian time via an auto-regulatory feedback loop in which the activation of Period (Per) and Cryptochrome genes is periodically suppressed by their own protein products. Casein kinase 1 (CK1) enzymes have a critical role in circadian pacemaking because they phosphorylate PER proteins and thereby direct their proteasomal degradation. In human pedigrees, individual mutations in either hCK1 or hPER2 lead to advanced sleep phase disorders, whereas in rodents, the Tau mutation of CK1 epsilon (CK1ϵ(Tau)) accelerates rest-activity cycles and shortens the period of the SCN molecular pacemaker. Biochemical analyses of recombinant PER proteins in cultured cells and endogenous proteins in peripheral tissues have identified PER1 and PER2, but not PER3, as direct substrates of CK1ϵ. The purpose of this study, therefore, was to determine the relative contributions of endogenous PER proteins to the period-accelerating effects of CK1ϵ(Tau), both in vivo and in vitro. CK1ϵ(Tau) mice were mated onto Per1-, Per2-, and Per1-Per2 (Per1/2) double-null backgrounds, in all cases carrying the Per1-luciferase bioluminescent circadian reporter gene. Mice lacking both PER1 and PER2 were behaviorally arrhythmic, confirming the inadequacy of PER3 as a circadian factor. Individual loss of either PER1 or PER2 had no significant effect on the circadian period or quality of wheel-running behavior, and CK1ϵ(Tau) accelerated behavioral rhythms in both Per1- and Per2-null mice. CK1ϵ(Tau) also accelerated in vitro molecular pacemaking in SCN lacking either PER1 or PER2, with a greater effect in PER2-dependent (i.e., Per1-null) SCN than in PER1-dependent slices. In double-null slices, some SCN were arrhythmic, whereas others exhibited transient rhythms, which trended nonsignificantly toward a shorter period. Both short-period and long-period rhythms could be identified in individual SCN neurons imaged by charge-coupled device camera. CK1ϵ(Tau) had no effect, however, on SCN-level or individual neuronal rhythms in the absence of PER1 and PER2. Thus, the CK1ϵ(Tau) allele has divergent actions, acting via both endogenous PER1 and PER2, but not PER3 protein, to mediate its circadian actions in vivo. Moreover, PER-independent cellular oscillations may contribute to pacemaking, but they are unstable and imprecise, and are not affected by the Tau mutation.